Shoot to kill - Craig, James, 1964-
When French gangster Tuco Martinez threatens Carlyle and his family, the inspector has to call on the resources and skills of Dominic Silver to try and see him off. But Dom won't do all the dirty work and so Carlyle has to go into hiding. Cut off from his home turf, both literally and metaphorically, Carlyle struggles to cope with the situation while meanwhile, back in London, the charismatic major, Christian Holroyd, is finally spiralling completely out of control..